REGISTRO CONTABLE DE LA CUENTA EFECTIVO Y EQUIVALENTE DE EFECTIVO DE LAS FARMACIAS “CRUZ AZUL” ZONA BABAHOYO – FRANQUICIADO FARMADESCUENTO - AVILÉS NIVELA, KERLY BELÉN (2018)
This case study is about the "Accounting record of the effective account and cash equivalent of the "Cruz Azul" pharmacies Babahoyo area - franchisee Farmadescuento. The excess of missing, the defective structuring in the collection of deposits and closures of boxes; voluntary prolongation (without remuneration) of the hours of work in the auxiliary treasury of the Babahoyo area, and deficient policy for the collection of the shortages, have been the reasons why this topic was chosen as a case study that was carried out under the accounting management research line. The techniques used to acquire information were: observation, interview and virtual research The observation allowed to know how the treasury assistant handles the issue of missing, leftovers, cross-dollar and late receipt of deposits and cash closures. The interview was directed to the pharmacy personnel, they were conducted by telephone and the called "face to face", thus knowing the problem of missing from the source that originates. Virtual research consented to make use of sites and books downloaded from the web that they allowed to obtain a much wider vision of the subject to study. Allowing to know those variables that directly and indirectly affect the account of cash and cash equivalent of "Cruz Azul" pharmacies in the Babahoyo area - Franchisee Franchisee Farmadescuento Franquiciado that is currently among the 1000 Companies that evolved their income from 2014 to 2016, according to the magazine Glance 2017